Study of Equipment Prices in the Power Sector - Pauschert, Dirk (World Bank, Washington, DC, 2014)
Global economic growth, particularly from 2004 to 20071, has fueled an expansion in the construction of industrial, power plant, and manufacturing facilities in the United States and a dramatic escalation in the construction of these types of heavy construction projects overseas. In addition, the increase in demand for oil by rapidly growing countries such as China and India and the falling value of the dollar has resulted in an unprecedented rise in the price of oil. This has significantly accelerated oil exploration and resulted in capacity-expansion projects at existing oil refineries. The combination of power plant, infrastructure, and oil-related projects has resulted in significant growth in demand for boilers, rotating equipment, piping, structural steel, concrete, electrical components, and electric wiring. In light of this finding, this study compared the cost of power plants without market demand to the actual costs incurred in constructing power plants. The results indicate that owners are purchasing plants in a sellers' market, where unprecedented demand has resulted in market price premiums in the range of 15 percentage points above material, equipment, and labor escalation.